2019
DOI: 10.1097/meg.0000000000001356
|View full text |Cite
|
Sign up to set email alerts
|

Early vedolizumab trough levels at induction in inflammatory bowel disease patients with treatment failure during maintenance

Abstract: Background Vedolizumab (VDZ) is effective as an induction and maintenance treatment for Crohn's disease and ulcerative colitis, but, as observed with antitumour necrosis factor-α (anti-TNFα) agents, some patients are nonetheless experiencing loss of response.Objective The aim of this study was to investigate the impact of the pharmacokinetics of VDZ during induction on long-term treatment response. Patients and methods This study focused on a single cohort of 103 inflammatory bowel disease patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
6
20
4
Order By: Relevance
“…A threshold of 18 μg/mL was identified as the optimal vedolizumab concentration at week 6 to reach mucosal healing. A similar concentration–response relationship was observed in a study by Liefferinckx et al . with overall higher vedolizumab concentrations.…”
Section: Drug Concentration Thresholds To Achieve Endoscopic Outcomessupporting
confidence: 87%
See 1 more Smart Citation
“…A threshold of 18 μg/mL was identified as the optimal vedolizumab concentration at week 6 to reach mucosal healing. A similar concentration–response relationship was observed in a study by Liefferinckx et al . with overall higher vedolizumab concentrations.…”
Section: Drug Concentration Thresholds To Achieve Endoscopic Outcomessupporting
confidence: 87%
“…A threshold of 18 μg/mL was identified as the optimal vedolizumab concentration at week 6 to STATE of the ART reach mucosal healing. A similar concentration-response relationship was observed in a study by Liefferinckx et al 46 with overall higher vedolizumab concentrations. At week 6, patients achieving mucosal healing between weeks 14 and 54 had a higher vedolizumab concentration (41.7 μg/mL) compared with patients with mild (26 μg/mL) or severe endoscopic activity (20.8 μg/mL).…”
Section: Vedolizumabsupporting
confidence: 86%
“…Furthermore, they demonstrated a positive correlation between serum vedolizumab concentrations and serum albumin and an inverse correlation with C-reactive protein (CRP), fecal calprotectin, and body mass. Finally, immunogenicity was very low as only 3/55 (5.5%) patients had detectable antibodies to vedolizumab through the 52 weeks of follow-up using a drug-tolerant homogeneous mobility shift assay.These results are in line with previous studies, showing that higher vedolizumab concentrations, during both induction and maintenance treatments, are typically associated with superior therapeutic outcomes in patients with IBD (Table 1) [2][3][4][5][6][7][8]. The identification of clinically relevant vedolizumab thresholds is important as this would be the first step for applying both reactive and proactive TDMbased therapeutic algorithms.…”
supporting
confidence: 89%
“…These results are in line with previous studies, showing that higher vedolizumab concentrations, during both induction and maintenance treatments, are typically associated with superior therapeutic outcomes in patients with IBD (Table 1) [2][3][4][5][6][7][8]. The identification of clinically relevant vedolizumab thresholds is important as this would be the first step for applying both reactive and proactive TDMbased therapeutic algorithms.…”
supporting
confidence: 89%
“…More recent studies have shown that, at least in UC, patients achieving and maintaining clinical and endoscopic remission have significantly higher vedolizumab trough concentration during maintenance therapy than patients who do not respond [32][33][34][35][36][37][38][39]. Nevertheless, it remains plausible that further clinical and biological factors can influence the response to the drug.…”
Section: Introductionmentioning
confidence: 99%